1987
DOI: 10.1111/j.1471-0528.1987.tb03756.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E production by amniotic cells in relation to term and preterm labour

Abstract: Summary. The rate of prostaglandin E (PGE) production was measured in collagenase‐dispersed amniotic cells obtained from 14 women after spontaneous labour at term—seven after spontaneous preterm labour, nine after delivery by elective caesarean section at term and six after induction of labour at term. Cells were incubated with and without arachidonic acid and PGE was estimated by specific radioimmunoassay. Basal PGE output (pmol/106 cells per 3 h) was highest in the spontaneous labour group, 27·5 (SEM 5·5) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There were a few incongruent findings for PGE 2 . Lopez-Bernal et al 1987 found that PGE 2 was produced by chorion and decidual cells and that the production was increased by arachidonic acid treatment, but found no significant change in PGE 2 protein level in labor versus no labor 73 . Similarly, Satoh et al 1981 found that the PGE 2 protein production was the same between labor and non-labor amnion, decidua, and myometrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a few incongruent findings for PGE 2 . Lopez-Bernal et al 1987 found that PGE 2 was produced by chorion and decidual cells and that the production was increased by arachidonic acid treatment, but found no significant change in PGE 2 protein level in labor versus no labor 73 . Similarly, Satoh et al 1981 found that the PGE 2 protein production was the same between labor and non-labor amnion, decidua, and myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of articles reviewed found an increase in PGE 2 protein at term labor or with in vitro simulated labor. 21, 30, 36, 39, 62, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the fetal membranes are a major source of intrauterine prostaglandins in labour (Kierse & Turnbull 1976, Skinner & Challis 1985. The amnion and decidua are the main synthetic tissues (Okazaki et al 1981, Lopez-Bernal et al 1987, whereas chorionic trophoblast cells have high levels of prostaglandin dehydrogenase to convert the primary prostaglandins to inactive metabolites (Sangha et al 1994). Expression of prostaglandin pathway synthetic enzymes has been clearly demonstrated in both amnion and decidual cells (Mitchell 1987, Romero et al 1988, with increased levels of these enzymes found in the latter stages of pregnancy (Slater et al 1995, and in association with labour (Khan et al 1992, Fuentes et al 1996.…”
Section: Introductionmentioning
confidence: 99%